Stereotactic Ablative Radiotherapy (SABR) in Patients with Medically Inoperable Peripheral Early Stage Lung Cancer: Outcomes for the First UK SABR Cohort. Issue 1 (January 2016) - Murray, L.; Ramasamy, S.; Lilley, J.; Snee, M.; Clarke, K.; Musunuru, H.B.; Needham, A.; Turner, R.; Sangha, V.; Flatley, M.; Franks, K.
Abstract: Aims: To report outcomes for the first UK cohort treated for early stage peripheral lung cancer using stereotactic ablative radiotherapy (SABR). Materials and methods: Patients were included who received SABR between May 2009 and May 2012. Electronic medical records were reviewed for baseline characteristics, treatment details and outcomes. Patients were treated according to the UK SABR Consortium Guidelines. Univariate and multivariate Cox regression was used to determine factors that influenced overall survival and local control. Results: In total, 273 patients received SABR for 288 lesions in the time period examined. The median follow-up was 19.7 months. The median overall survival for all patients was 27.3 months, with 1, 2 and 3 year overall survival of 78.0, 54.9 and 38.6%, respectively. The 1, 2 and 3 year rates of local control were 98.2, 95.7 and 95.7%, respectively. All patients completed the planned course of treatment and rates of Common Toxicity Criteria grade 3+ toxicity were low. On multivariate analysis, patients with Medical Research Council (MRC) breathlessness scores of 3–5 had worse overall survival compared with patients with scores of 1–2 (hazard ratio: 2.10; 95% confidence interval: 1.25–3.59) and the presence of histological diagnosis conferred improved overall survival (hazard ratio: 0.54; 95% confidence interval: 0.31–0.93), probably reflecting that patients who are considered well enough to undergo biopsy are generally fitter overall. No factors were identified that significantly influenced local control. Conclusions: SABR is an effective and well-tolerated treatment option for patients with early stage peripheral lung cancer who are not suitable for surgery. No patient cohort was identified in whom SABR was considered inappropriate. This series adds to the existing positive data that support SABR for this patient group. Highlights: Outcomes for the first UK lung stereotactic ablative radiotherapy cohort are presented. Excellent rates of local control were observed. Treatment was well tolerated with low rates of grade 3 or greater toxicity. Patients with high breathlessness scores or no histology had worse overall survival. No factors were identified that had a significant effect on local control.